HLF and hTERT cooperatively enable partial immortalization of human hematopoietic stem and progenitor cells - Azhagiri, Manoj Kumar K.; Verhoeyen, Els; Mohankumar, Kumarasamypet Murugesan; Marepally, Srujan Kumar; Venkatesan, Vigneshwaran; Thangavel, Saravanabhavan (Frontiers in Bioengineering and Biotechnology, 2026)
Hematopoietic stem and progenitor cells (HSPCs), residing at the apex of the hematopoietic hierarchy, are critical for the generation of all blood and immune cell lineages. This unique capacity makes HSPCs indispensable for advancing cell and gene therapies aimed at correcting defects across hematopoietic lineages. However, current gene therapy development is constrained by the requirement for fresh primary HSPCs, hindering the breadth of preclinical validation. While several hematopoietic lineages have been immortalized to facilitate research, the stable immortalization of human HSPCs remains unreported. Here, we demonstrate that combinatorial overexpression of HLF, a key regulator of stem cell maintenance, and hTERT, a telomere maintenance factor in primitive human HSCs, supported by BaEV-mediated transduction and optimized culture conditions, yields partial immortalization of HSPCs. These genetically modified cells sustained for up to 70 days and exhibited limited differentiation towards erythroid, megakaryocytic, and macrophage lineages. Our model establishes a protocol for generating primary cell like context for testing gene therapy strategies, enabling functional assessment in both undifferentiated HSPCs and their lineage-committed progeny.